Sistem Informasi Kepegawai Pada Puskesmas Semendawai Barat Menggunakan Metode Agile - Aulia, Beta; Sanmorino, Ahmad; Saluza, Imelda (Jurnal Ilmiah Informatika Global, 2025)
Employee information systems are an essential element in supporting efficient and structured administrative and employee data management processes. This study aims to design and develop a web-based personnel information system at Semendawai Barat Public Health Center using the Agile method. The system is developed to facilitate the management of employee data, user data, position or division data, daily attendance, leave requests, and employee activity reports. Problems commonly encountered in manual systems, such as data loss, delayed information access, and recording errors, form the basis for the need to develop an integrated digital system. The Agile method was chosen because it allows for an iterative and flexible development process that involves users at every stage, enabling the system to be tailored directly to user needs. This study includes system requirements analysis, interface design, implementation of core features, and system testing by users. The results of this research indicate that the developed system runs well, is user-friendly, and helps accelerate the personnel administration process. It also minimizes recording errors and reduces the risk of data loss. Therefore, this web-based personnel information system is expected to improve the performance and work efficiency of the staff at Semendawai Barat Public Health Center in managing personnel data comprehensively.